PODCAST SEBAGAI MEDIA PEMBELAJARAN KETERAMPILAN MENYIMAK CERITA DONGENG BAGI SISWA KELAS II SDN PASIRANGIN - Pratiwi, Tiara Putri; Yuniarti, Yeni; Rakhmayanti, Fully (Jurnal Kajian Pembelajaran dan Keilmuan, 2022)
Listening skills are the most basic skills that must be possessed by students. The low listening skills of the second grade students of SDN Pasirangin on the material of fairy tales and the lack of use of media are the background of this study. The purposes of the research are (1) to find out the use of podcast media in learning to listen the fairy tales and (2) to find out the learning outcomes from the use of podcast media in learning to listen the fairy tales. Learning media is an important component in learning. Podcast media as an audio-digital based learning media is expected to improve students"™ listening skills. The method used in this research is qualitative descriptive method. Data collection techniques carried out are observation, questionnaires, interviews and documentation. The results of the study are the use of podcast media in learning to listen the fairy tales can make the learning more fun, effective, interesting, and make students more enthusiastic in learning. In addition, the results of this study indicate the students"™ personal interests and the use of podcast media by teacher in learning are the factors that influence the student listening process. Based on the result of the study, it can be concluded that podcast media can be an alternative innovative learning media that can be used by teacher in the learning process, especially listening learning so that students"™ listening skills become better.